IMPACT OF PRETRANSPLANT DONOR AND RECIPIENT CYTOMEGALOVIRUS SEROSTATUS ON OUTCOME FOR MULTIPLE MYELOMA PATIENTS UNDERGOING REDUCED INTENSITY CONDITIONING ALLOGENEIC STEM CELL TRANSPLANTATION. - Jean Elcheikh (Mediterranean Journal of Hematology and Infectious Diseases)
To investigate the impact of pre-transplant CMV serostatus of donor or recipient on outcome of patients undergoing allogeneic hematopoietic stem cell transplantation (Allo-SCT) for Multiple Myeloma (MM). To our knowledge no data are available in the literature about this issue.